Budgeting Training through the Business Financial Management System (SIPEKU) Program for MSMEs at the Pujasera Merah Canteen, UIN Bandung - Putri Zafira Ruhliandini; Ahmad Nur Kamal; Hadi Jayadi; Thoriq Rifky Alghifary (Unram Journal of Community Service, 2026)
The fundamental issue faced by Canteen MSMEs at Pujasera Merah UIN Bandung is weak financial management, characterized by inconsistent bookkeeping and the commingling of business and personal finances without formal budgeting. This community service project aims to enhance financial literacy and managerial skills among partners through the implementation of the Business Financial Management System (SIPEKU) Program. The implementation method employed a participatory learning approach, encompassing intensive training, simulations of Microsoft Excel-based digital toolkits, and continuous mentoring. The results indicate a significant increase in participant enthusiasm and digital proficiency, with business owners successfully operating budgeting templates via their smartphones. Based on a two-month monitoring period, a behavioral transformation was observed, shifting from initial resistance to active adoption. Participants reported positive outcomes, including cash flow transparency, accurate business measurement, and accelerated decision-making capabilities. This program concludes that simple digital budgeting systems are effective in fostering peace of mind and clarifying business growth visions for MSME entrepreneurs.